IL‐38 attenuates myocardial ischemia–reperfusion injury by inhibiting macrophage inflammation - Yuzhen Wei; Junhui Xing; Xin Su; Xiangrao Li; Xiaofei Yan; Jiangtao Zhao; Hailong Tao (Immunity, Inflammation and Disease)
Abstract Background Reperfusion therapy is the most effective approach to resolve coronary occlusion, but myocardial injury caused by excessive inflammation during myocardial ischemia–reperfusion will also pose a new threat to health. Our prior study revealed the expression pattern of interleukin‐38 (IL‐38) in the peripheral blood serum of patients with ischemic cardiomyopathy and the role of IL‐38 in acute myocardial infarction in mice. However, its role and potential mechanisms in myocardial ischemia/reperfusion injury (MIRI) remain to be determined. Methods and Results The left anterior descending artery of C57BL/6 mice was transiently ligated to induce the MIRI model. We found that MIRI induced the expression of endogenous IL‐38, which was mainly produced by locally infiltrating macrophages. Overexpression of IL‐38 in C57BL/6 mice attenuated inflammatory injury and decreased myocardial apoptosis after myocardial ischemia–reperfusion. Furthermore, IL‐38 inhibited lipopolysaccharide‐induced macrophage inflammation in vitro. Cardiomyocytes cocultured with the supernatant of IL‐38‐ and troponin I‐treated macrophages showed a lower rate of apoptosis than controls. Conclusions IL‐38 attenuates MIRI by inhibiting macrophage inflammation. This inhibitory effect may be partially achieved by inhibiting the activation of NOD‐like receptor pyrin domain‐related protein 3 inflammasome, resulting in decreased expression of inflammatory factors and reduced cardiomyocyte apoptosis.